Duration of second victim symptoms in the aftermath of a patient safety incident and association with the level of patient harm: a cross-sectional study in the Netherlands. Issue 7 (9th July 2019) - Vanhaecht, Kris; Seys, Deborah; Schouten, Loes; Bruyneel, Luk; Coeckelberghs, Ellen; Panella, Massimiliano; Zeeman, Gerda
Abstract : Objectives: To describe healthcare providers' symptoms evoked by patient safety incidents (PSIs), the duration of these symptoms and the association with the degree of patient harm caused by the incident. Design: Cross-sectional survey. Setting: 32 Dutch hospitals that participate in the 'Peer Support Collaborative'. Participants: 4369 healthcare providers (1619 doctors and 2750 nurses) involved in a PSI at any time during their career. Interventions: All doctors and nurses working in direct patient care in the 32 participating hospitals were invited via email to participate in an online survey. Primary and secondary outcome measures: Prevalence of symptoms, symptom duration and its relationship with the degree of patient harm. Results: In total 4369 respondents were involved in a PSI and completely filled in the questionnaire. Of these, 462 reported having been involved in a PSI with permanent harm or death during the last 6 months. This had a personal, professional impact as well as impact on effective teamwork requirements. The impact of a PSI increased when the degree of patient harm was more severe. The most common symptom was hypervigilance (53.0%). The three most common symptoms related to teamwork were having doubts about knowledge and skill (27.0%), feeling unable to provide quality care (15.6%) and feeling uncomfortable within the team (15.5%). PSI with permanent harm or death was related to eightfold higher likelihood of provider-related symptoms lasting for more than 1 month and ninefold lasting longer than 6 months compared with symptoms reported when the PSI caused no harm. Conclusion: The impact of PSI remains an underestimated problem. The higher the degree of harm, the longer the symptoms last. Future studies should evaluate how these data can be integrated in evidence-based support systems.